AI-Powered MetaHuman Interviewer: Serious Game for Student Job Interview Skills - Kansada Mongkoljaturong; Mesa Manitsakulwong; Samart Moodleah (IEEE Access, 2025)
Effective interview preparation is critical for university graduates entering a competitive job market, yet traditional methods often lack sufficient realism and interactivity. This paper presents the development and evaluation of an innovative serious game, the Interactive Interview Assistant Application (IIAA), designed to address this gap. The IIAA simulates job interviews using an AI-driven digital human interviewer powered by MetaHuman technology, a Large Language Model (LLM) for dynamic dialogue, and integrated Speech-to-Text, Text-to-Speech, and Speech-to-Animation systems, offering a personalized and immersive practice environment. The system was evaluated with senior undergraduate students across three distinct career paths (UX/UI Design, Software Engineering, Game Development). The evaluation focused on system performance, overall usability, and qualitative user feedback. Results indicate that the IIAA successfully creates an engaging and realistic simulation, with users reporting high satisfaction regarding its ability to emulate real-world interview scenarios and provide valuable, actionable feedback. While identified performance latencies related to high-definition 3D animation and voice processing require further optimization, the study underscores the significant potential of this approach. This research demonstrates that sophisticated game-based tools can substantially enhance interview preparedness, thereby improving student confidence and readiness for professional employment.
Keywords: Educational Games and Gamification; AI in Service Interactions; Artificial Intelligence in Healthcare and Education